Adverse Childhood Experiences and Symptoms of Urologic Chronic Pelvic Pain Syndrome: A Multidisciplinary Approach to the Study of Chronic Pelvic Pain Research Network Study - Schrepf, Andrew (Ann Behav Med, 2018)
BACKGROUND: Adverse Childhood Experiences (ACEs) such as sexual and physical violence, serious illness, and bereavement have been linked to number of chronic pain conditions in adulthood, and specifically to urologic chronic pelvic pain syndrome (UCPPS). PURPOSE: We sought to characterize the prevalence of ACEs in UCPPS using a large well-characterized cohort in comparison with a group of healthy controls. We also sought to determine the association of ACE severity with psychological factors known to impact pain and to determine whether ACEs are associated with patterns of improvement or worsening of symptom over a year of naturalistic observation. METHODS: For longitudinal analyses we used functional clusters identifying broad classes of (a) improved, (b) worsened, and (c) stable groups for genitourinary pain and urinary symptoms. We employed a mediation/path analysis framework to determine whether ACEs influenced 1 year outcomes directly, or indirectly through worse perceptions of physical well-being. RESULTS: ACE severity was elevated in UCPPS (n = 421) participants compared with healthy controls (n = 414; p < .001), and was most strongly associated with factors associated with complex chronic pain, including more diffuse pain, comorbid functional symptoms/syndromes, and worse perceived physical well-being (all p < .001). Finally, worse physical well-being mediated the relationship between ACE severity and less likelihood of painful symptom improvement (OR = .871, p = .007)) and a greater likelihood of painful symptom worsening (OR = 1.249, p = .003) at 1 year. CONCLUSIONS: These results confirm the association between ACEs and UCPPS symptoms, and suggest potential targets for therapeutic interventions in UCPPS. CLINICAL TRIAL REGISTRATION: NCT01098279.